Genetic Separation of Listeria monocytogenes Causing Central Nervous System Infections in Animals - Aguilar-Bultet, Lisandra; Nicholson, Pamela; Rychener, Lorenz; Dreyer, Margaux; Gözel, Bulent; Origgi, Francesco C.; Oevermann, Anna; Frey, Joachim; Falquet, Laurent (Frontiers in Cellular and Infection Microbiology, 2018)
Listeria monocytogenes is a foodborne pathogen that causes abortion, septicemia, gastroenteritis and central nervous system (CNS) infections in ruminants and humans. L. monocytogenes strains mainly belong to two distinct phylogenetic groups, named lineages I and II. In general, clinical cases in humans and animals, in particular CNS infections, are caused by lineage I strains, while most of the environmental and food strains belong to lineage II. Little is known about why lineage I is more virulent than lineage II, even though various molecular factors and mechanisms associated with pathogenesis are known. In this study, we have used a variety of whole genome sequence analyses and comparative genomic tools in order to find characteristics that distinguish lineage I from lineage II strains and CNS infection strains from non-CNS strains. We analyzed 225 strains and identified single nucleotide variants between lineages I and II, as well as differences in the gene content. Using a novel approach based on Reads Per Kilobase per Million Mapped (RPKM), we identified 167 genes predominantly absent in lineage II but present in lineage I. These genes are mostly encoding for membrane-associated proteins. Additionally, we found 77 genes that are largely absent in the non-CNS associated strains, while 39 genes are especially lacking in our defined “non-clinical” group. Based on the RPKM analysis and the metadata linked to the L. monocytogenes strains, we identified 6 genes potentially associated with CNS cases, which include a transcriptional regulator, an ABC transporter and a non-coding RNA. Although there is not a clear separation between pathogenic and non-pathogenic strains based on phylogenetic lineages, the presence of the genes identified in our study reveals potential pathogenesis traits in ruminant L. monocytogenes strains. Ultimately, the differences that we have found in our study will help steer future studies in understanding the virulence mechanisms of the most pathogenic L. monocytogenes strains.